How important is health literacy influencing husband’s actions in women’s health? - Asy Syafa Mahfuzhah (BKM Public Health and Community Medicine, 2021)
Objective: This study aims to explore the involvement of the husband's role based on the level of health literacy towards women's health and the fulfillment of basic family health needs. Content: Currently, there are limited health programs that involve the role of husbands, especially health education regarding maternal and child health. Health education relating to women's health is not a priority for Primary Health Care. Several factors influence the low level of health literacy, such as rural residence, education level, and family network that influence women's decision making to visit health services. So the importance of peer and community networks through antenatal care groups, for example, in collaboration with village midwives or health workers. In addition, the community leaders, cadres, religious leaders are some source who are close to the community and could potentially improve health literacy and husband's knowledge. There are potential obstacles that can occur, there are the lack of motivation for husbands to attend health education held by PHC, and the lack of health education programs regarding women's health that specifically involve husbands. Conclusion: The importance of health literacy among husband to reduce the risk of negative health outcomes for women by increasing understanding among key families and community members. Husbands who are highly educated will have more empathy for women's health than those with low or no knowledge. Husbands play an important role in maintaining women's health, especially in relation to the health treatment in the health service, such as in prevention and early detection of maternal and child health problems.